Potential Activities of Centella asiatica Leaf Extract against Pathogenic Bacteria-Associated Biofilms and Its Anti-Inflammatory Effects - Piriya Chonsut; Chonticha Romyasamit; Atthaphon Konyanee; Nattisa Niyomtham; Lavanya Goodla; Auemphon Mordmuang (Advances in Pharmacological and Pharmaceutical Sciences)
The medicinal value of Centella asiatica leaf extract was evaluated as an alternative treatment. The chemical composition of the leaf extract was analyzed, and the biological activities were determined. High-performance liquid chromatography coupled with a photodiode array detector (HPLC-PDA) was used to identify the asiatic acid, madasiatic acid, and madecassic acid/Brahmic acid isolated from the ethanolic extract. The plant extract at 25 mg/disk was found to inhibit both Gram-positive and Gram-negative pathogenic bacteria by the agar disk diffusion test. The MIC and MBC of the ethanolic extracts were better than those of the aqueous extracts. The ethanolic extracts showed antibacterial activity against Gram-positive bacteria with MICs and MBCs ranging from 1.024 to 2.048 mg/mL and 2.048 to 4.096 mg/mL, respectively. The remarkable antibacterial activities were observed against S. mutans. The ethanolic extract at a concentration of 1/2 × MIC exhibited the inhibition effect on S. mutans biofilm formation like the activity of 0.2% chlorhexidine and significantly modified hydrophobicity of the bacterial cell surface. The effects were confirmed via molecular docking analysis. The binding affinities of asiatic acid, madecassic acid, and madasiatic acid with glucosyltransferase C (GtfC) of S. mutans exhibited superior strength in comparison with alpha-acarbose and chlorhexidine. Moreover, the nitric oxide (NO) secretion of RAW247.6 cells was determined after treating the cells with concentrations of the extract. The C. asiatica ethanolic extract can inhibit the secretion of NO, which can inhibit the inflammatory process. The findings indicate the applications of the C. asiatica ethanolic extract as the alternative anti-S. mutans agent and could be used for further formulation for the treatment and prevention of dental diseases and inflammatory injury in the oral cavity.